Exposition of an unusual presentation: a case report of benign tumor arising from an uncommon origin - Velayutham, Prabu; Palani, Vignesh; Saxena, Sunil Kumar; Balan, Hema (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
The inverted papilloma is a benign neoplasm that originates from the sinonasal mucosa, which is also referred to as a Ringertz tumor. It mostly affects men, falling within the age groups of 50 to 60 years. Our case is rare of its type as it was present in an unusual site, which is from the middle turbinate. Here in our study, we report a case of a 25-year-old female presented to the ENT outpatient department with complaints of left-sided nasal obstruction for 4 years. The patient had noticed a pinkish mass in the left nasal cavity. She complained of intermittent episodes of left-sided nasal bleeds. The patient was planned for functional endoscopic sinus surgery with a partial middle turbinectomy under general anaesthesia. Histopathological examination showed polypoidal tissue fragments lined predominantly by non-keratinized stratified squamous epithelium, along with focal areas lined by respiratory-type pseudostratified columnar epithelium and transitional epithelium, with multiple foci of inward proliferation of the epithelium in the form of nests into the underlying sub epithelium with an intact basement membrane, which is suggestive of inverted papilloma. After one week of postoperative follow-up, patient’s symptoms of nasal obstruction were relieved. During the subsequent 6 months of follow-up, the patient had no evidence of tumor recurrence. In our case, we wanted to emphasize that not all cases that do not involve the maxillary sinus or the medial wall of the maxilla on a CT scan require medial maxillectomy.